(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
The article scientifically substantiates the criteria for the formation of a culture of professional communication of young process engineers. Communication performs various tasks. Different authors identify different tasks of communication. g.m. Andreeva lists communicative, interactive and perceptual tasks. Communication performs information-communicative, managerial-communicative, perceptual-effective and affective-expressive (emotional self-expression) tasks.